Analisis Kesesuaian Persebaran Keruangan Ritel Chain StoreDengan RTRW Kota Yogyakarta 2016 - Wetty, Maria Pramudita, Drs. M. Musiyam, M.TP (2016)
Yogyakarta is a city that is inseparable from the development Chain store. The study "Analysis Of Suitability Spatial Spread Of Retail Chain Store Towards Spatial Plans Of Yogyakarta City 2016" aims to identify the spatial distribution pattern of retail chain stores in the city of Yogyakarta and analyze the suitability of retail chain store with the Spatial Yogyakarta The method used in this research is descriptive qualitative method. Descriptive and qualitative analysis methods to analyze describe and summarize a variety of conditions, the situation of the various data collected in the form of census results or observations of the issues, which occur in the field. In this study, also conducted a census of the three objects that store Chain Alfamart, Circke K and Indomaret spread in the city of Yogyakarta and total reached 54 objects. This study showed the spatial distribution pattern of Chain stores in Yogyakarta that are associated with housing, education center, tourism center, and a large retail opponent lies on collector roads classification of 55.55%. Conformity with the Spatial Distribution Chain stores in the city of Yogyakarta reached 88.89% and there is still non-conformance of 11.11%. This discrepancy found in the Wirobrajan District, Umbulharjo District, and Gondokusuman District, which objects Chain store, stands near to the center of education. Therefore, development of chain store objects that are in the densely populated settlements and local boarding house for students. So with the development of chain stores are located close to the center of activities of citizens, able to meet the economic needs such as food and other primary needs to the surrounding population.